Robotic assisted minimally invasive thymectomy with simultaneous bilateral thoracoscopy and contralateral phrenic nerve visualization - Hess, Nicholas R.; Baker, Nicholas; Levy, Ryan M.; Pennathur, Arjun; Christie, Neil A.; Luketich, James D.; Sarkaria, Inderpal S. (Journal of Thoracic Disease; Vol 12, No 2 (February 19, 2020): Journal of Thoracic Disease [The 4th Ruijin International Thoracic Symposium (RITS 2019): Complex Robotic Thoracic Surgery], 2020)
Background: Thoracoscopic approaches to thymectomy and anterior mediastinal mass resection has become increasingly common due to the potential for decreased blood loss and hospital length of stay. However, contralateral mediastinal and phrenic nerve visualization if often difficult from these unilateral approaches, which may affect the ability to achieve a full phrenic to phrenic dissection Herein, we present our early experience of robotic assisted minimally invasive thymectomy (RAMIT) with simultaneous bilateral thoracoscopy and contralateral phrenic nerve visualization. Methods: This was a retrospective review of all sequential patients undergoing RAMIT with simultaneous bilateral thoracoscopy from January 2015 to May 2016. This study was approved by our Institutional Review Board (PRO15080367). Individual patient consent was waived. Results: Twenty-six patients [median age 58 (range, 29–76) years] were included in this study. Sixteen operations were performed for anterior mediastinal mass, 7 for non-thymomatous myasthenia gravis, and 3 for concurrent myasthenia gravis and thymoma. Median blood loss and hospital stay were 25 mL (range, 3–150 mL) and 3 days (range, 2–8 days), respectively. Twenty-one (80.8%) patients experienced an uncomplicated hospital course. The highest graded complication by Clavien Dindo Classification was a grade III due to pleural effusion requiring drainage via pleural catheter. One patient experienced asymptomatic hemidiaphram palsy postoperatively. There were no 90-day postoperative deaths. Conclusions: RAMIT with simultaneous bilateral thoracoscopy is a feasible approach that may allow for enhanced visualization and more complete thymic resection compared to existing unilateral minimally invasive operations. Comparative studies and long-term follow up are needed to adequately assess the potential benefits of RAMIT.